Maternal–Foetal Effects of Exposure to Bisphenol A: Outcomes and Long-Term Consequences - Henrique Eloi Costa; Ines Medeiros; Melissa Mariana; Elisa Cairrao (Applied Sciences)
Exposure to bisphenol A (BPA), one of the most widely produced plasticisers, can have a major effect on the growing embryo and the mother during pregnancy; as this is the most vulnerable period, the cutoff established in the legislation does not take this factor into account. Thus, this narrative review aims to highlight the consequences for the foetus and the pregnant woman of maternal and foetal exposure to BPA by analysing epidemiological and experimental studies on humans. Extensive research has examined the effects of BPA on several systems outcomes. Specifically, BPA exposure affects the immune system of the offspring and promotes the development of respiratory diseases, including asthma and wheezing. Moreover, BPA has been negatively associated with children’s neurodevelopment, leading to behavioural changes; autism; and reproductive changes, mainly deviations in anogenital distance, sexual hormone levels and sexual maturation, which can result in infertility. Furthermore, in mothers, BPA exposure may be linked to pre-eclampsia and gestational diabetes mellitus and affects birth parameters, leading to a higher risk of preterm delivery, shorter birth lengths and lower birth weights, although the results were not always consistent. These results demonstrate the urgent need for stricter legislation banning the use of BPA during pregnancy to reduce the hazards to the health and development of the foetus and the unborn child.